Effect on base pressure in suddenly expanded flows with variable location of microjets - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Rathakrishnan, E. (ijcrr.com, 2012)
This paper presents results of an experimental investigation to study the effectiveness of micro jets to control the base pressure in suddenly expanded axi-symmetric ducts when the micro jets are placed at different location (i.e. at the base, at the duct, and at base as well as at the duct). The purpose of this study is to study the individual as well as the combined effectiveness of the micro jet as the active controller of the base pressure. The area ratio of the present study is 3.24. The nozzle generating the above jet Mach numbers were operated with nozzle pressure ratio (NPR) in the range 3 to 11. In addition to base pressure, wall pressure field along the duct was also studied. As high as 70 percent increase in base pressure was achieved for Mach number 2.58 at NPR 11 when the micro jets are placed at the base as well as the duct.